Synergistic Co3O4 cocatalyst integration in BiVO4 photoanodes for high-efficiency photoelectrochemical water splitting to produce green hydrogen - Castañeda, Victor Zamora (2026)
The global energy sector faces critical challenges that demand clean and sustainable alternatives. Hydrogen has emerged as a promising alternative, with photoelectrochemical (PEC) water splitting offering a viable pathway for solar-driven hydrogen production. Among the components of PEC systems, photoanodes remain a major performance bottleneck. In this master’s thesis, bismuth vanadate (BiVO4, BVO) photoanodes were fabricated by RF magnetron sputtering, with particular emphasis on evaluating the influence of the O2/Ar gas ratio during sputtering deposition. Optimizing the O2/Ar gas ratio during deposition enabled the growth of stoichiometrically controlled BiVO4 thin films with tailored defect structures. The optimal condition (100% O2) resulted in a fourfold increase in PEC performance, achieving a photocurrent density of 1.6 mA cm-2 at 1.23 V vs. RHE. This improvement reflects enhanced charge-transfer efficiency at the semiconductor-electrolyte interface and a simultaneous reduction in both bulk and surface recombination. Furthermore, optimizing the gas ratio led to a twofold improvement in charge-separation efficiency, increasing it to approximately 40-60%. Following sputtering deposition and annealing treatment, the photoanodes were further modified with a Co3O4 cocatalyst through hydrothermal synthesis to enhance their performance toward the water oxidation reaction. PEC measures revealed significant improvements in photocurrent density, onset potential, and both charge separation and injection efficiencies following Co3O4 modification with a maximum current of 2.27 mA cm-2 at 1.23 V vs. RHE. The BVO/Co3O4 photoanode showed reduced interfacial charge-transfer resistance under illumination and improved ABPE and IPCE, demonstrating more efficient photon-to-current conversion. Mott-Schottky and EIS analyses confirmed that the Co3O4 cocatalyst enhances interfacial charge transfer while suppressing carrier recombination, resulting in a marked improvement in PEC water-splitting efficiency. These findings highlight the critical role of gas-ratio-controlled BVO deposition in achieving highly efficient photoanodes for PEC applications. Additionally, the incorporation of Co3O4 as a surface cocatalyst further improves the activity of BVO photoanodes, providing a meaningful foundation for the development of next-generation, high-performance PEC systems.